PERANCANGAN SISTEM SMART GRID BERBASIS INTERNET OF THINGS UNTUK PENGELOLAAN LISTRIK YANG EFISIEN - Saputra, Thio (JURNAL TELISKA, 2025)
The use of energy in Indonesia is influenced by various factors, including history, economics, and geography, with a high dependence on fossil fuels despite declining oil reserves. The transition to clean energy sources, particularly solar energy through solar panels, has become a primary focus. Solar panels, which use semiconductor-based photovoltaic cells, serve to convert sunlight into electrical energy. The need for sustainable electricity drives the implementation of smart grid systems based on IoT technology, which enhances the efficiency and reliability of electricity distribution. This research explores the use of solar panels as an alternative power source by assessing the power output and efficiency of the system. The application of IoT allows for better automation and energy management. The research methods include needs analysis, system design, and the implementation of IoT technology for real-time monitoring. The results indicate that IoT-based smart grid systems can improve electricity management efficiently and sustainably.